De novo transcriptome sequencing and analysis of genes related to flavonoid metabolism in Abrus cantoniensis Hance - Weibin HUANG; Yu QIU; Zhixia CHEN; Cuimin HE; Xianmei XUE; Xujiang YUAN (Journal of Holistic Integrative Pharmacy)
Background and objective: Flavonoids are important botanical metabolites, which not only protect plants from harm but also exhibit a variety of biological activities. The aim of this study was to examine the transcriptomic profiles of Abrus cantoniensis (AC) and determine the differentially expressed genes (DEGs) of flavonoids in the roots (AC-R), stems (AC-S), mature leaves (AC-ML), and tender leaves (AC-TL) of this medicinal plant. Methods: Illumina sequencing technology was applied to sequence the transcriptome of AC. Bioinformatics tools were used to perform the de novo assembly, genes annotation, cluster analysis. Results: More than 99.70% clean reads with 57 325 assembled unigenes were obtained. A total of 36 947 unigenes (64.45%) were successfully annotated in the Nr, SwissProt, KOG, and KEGG databases; 8 269 unigenes were assigned to 132 pathways in the KEGG database. Differential gene analysis revealed meaningful differences in the number of up- and down-regulated genes among the different parts of AC, except between AC-R and AC-S. Cluster analysis of the expression patterns of the DEGs revealed different expression trends for 20 profiles among which 9 were remarkably enriched. The most obvious difference in gene expression among AC-R, AC-S, AC-ML, and AC-TL with respect to the biosynthesis of phenylpropanoids was detected upstream in the flavonoid metabolic pathway. Conclusion: This is the first study to provide information about the transcriptome profiles of AC and the DEGs of the flavonoid pathway in this plant.